Smart Consumer – A First Qualitative Step for a Scale Development - Jelea, Alexandra Raluca; Manolica, Adriana; Roman, Teodora; Bertea, Patricea Elena (Transformations In Business & Economics, 2025)
When looking into the exiting literature on the topic of smart consumer, we observed that there is a lack in having a clear definition of it, given the fact that the meaning of the term changed over years together with the emerge of technological advancement. In order to come with a broad understanding, we designed the first steps into the creation of a scale. The research combines and proposes multiple quantitative and qualitative methods like the Delphi method, mnemonic scores, pilot surveys, chromatic tables, and Cronbach alpha computations. The research takes you through all the stages in the creation of a scale. The items in the scale were generated by having semi-structured in-depth interviews with 21 experts in IT,C and Marketing fields. The items were generated from the in-depth interviews and are structured into dimensions. For each item in every dimension, we calculated Cronbach alpha and received a .95, which indicates an excellent reliability for the scale.
Keywords: smart consumer; scale development; Delphi method; e-communities; influencers; social media experts; generation Y; generation Z